Oman : Banking Sector Resilience - Prasad, Ananthakrishnan (IMF Working Papers; Working Paper, 2010)
This note assesses the impact of the global financial risks on Oman's banking system and highlights the remaining risks. It concludes that the liquidity and prudential measures introduced by the authorities mitigated the adverse effects of the crisis on the banking system. Banks continue to make profits despite higher provisioning. Stress tests confirm the resilience of the banking system to credit and market risks. Banks have limited exposure to derivatives and the majority of the off-balance sheet exposures are conventional and relatively secure. Interest rate risks are within an acceptable range.